Research on the optimization of collaborative mode under normalized epidemic prevention and control background in maternal and child health care institutions - Yang, Lichao; Ji, Cheng; Liu, Yang (Economics & Management Review, 2023)
Under the background of normalized epidemic prevention and control,Enhancing the coordination ability within maternal and child health care institutions can effectively reduce the losses caused by COVID – 19 outbreak and ensure the diagnosis and treatment activity in hospital orderly. This paper introduces the theory of collaboration governance and constructs the internal collaboration system of “policy collaboration, information collaboration, relationship collaboration and technology collaboration”, which provides reference for institutions to improve emergency management ability.